Soil Lead (Pb) in New Orleans: A Spatiotemporal and Racial Analysis - Egendorf, Sara Perl (Int J Environ Res Public Health, 2021)
Spatialized racial injustices drive morbidity and mortality inequalities. While many factors contribute to environmental injustices, Pb is particularly insidious, and is associated with cardio-vascular, kidney, and immune dysfunctions and is a leading cause of premature death worldwide. Here, we present a revised analysis from the New Orleans dataset of soil lead (SPb) and children’s blood Pb (BPb), which was systematically assembled for 2000–2005 and 2011–2016. We show the spatial–temporal inequities in SPb, children’s BPb, racial composition, and household income in New Orleans. Comparing medians for the inner city with outlying areas, soil Pb is 7.5 or 9.3 times greater, children’s blood Pb is ~2 times higher, and household income is lower. Between 2000–2005 and 2011–2016, a BPb decline occurred. Long-standing environmental and socioeconomic Pb exposure injustices have positioned Black populations at extreme risk of adverse health consequences. Given the overlapping health outcomes of Pb exposure with co-morbidities for conditions such as COVID-19, we suggest that further investigation be conducted on Pb exposure and pandemic-related mortality rates, particularly among Black populations. Mapping and remediating invisible environmental Pb provides a path forward for preventing future populations from developing a myriad of Pb-related health issues.